Microdialect and Group Signature in the Song of the Skylark Alauda arvensis - Briefer, Elodie; Rybak, Fanny; Aubin, Thierry (WBI Studies Repository, 2011)
The Skylark Alauda arvensis is a territorial species of open landscape in which pairs settle in stable and adjacent territories during the breeding season. Due to the heterogeneity of the habitat, territories are gathered in patches spaced by a few kilometres, in which each male produces very long and complex flight songs as a part of the territorial behaviour. We showed that, in a given patch, all the males (neighbours) share some particular sequences of syllables in their songs, whereas males settled in different patches (strangers) have almost no sequences in common. Such a phenomenon is known as microdialect. To test the hypothesis that these shared sequences support a group signature, we made playback experiments with ‘‘chimeric’’ signals: songs of strangers where the sequences shared by neighbours were artificially inserted. Behavioural responses to playbacks indicated a neighbour-stranger discrimination consistent with the dear enemy phenomenon, i.e. a reduced aggression toward neighbours compared to strangers. Furthermore, the same level of responses, observed when a ‘‘chimeric’’ song and a neighbour song were broadcast, indicated that shared sequences are recognized and identified as markers of the neighbourhood identity.